Gravitational corrections to light propagation in a perturbed FLRW universe and corresponding weak-lensing spectra - Cuesta-Lazaro, Carolina; Quera-Bofarull, Arnau; Reischke, Robert; Schäfer, Björn Malte (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. When the gravitational lensing of the large-scale structure is calculated from a cosmological model a few assumptions enter: (i) one assumes that the